尿酸値上昇アルツハイマー病モデルマウスにおけるグリア細胞の解析 - 富岡, 直子; 細山田, 真 (日本薬理学会年会要旨集, 2020)
Several epidemiological studies suggest that uric acid exerts a neuroprotective effect in neurodegenerative disease such as Parkinson's disease and Alzheimer's disease (AD). However, the molecular mechanism how uric acid affect the pathology and/or cognitive function in Alzheimer's disease remains unclear. In this study, we developed a combined mouse model by cross-breeding AppNL-G-F knock-in mouse（App-KI）which carries humanized amyloid βprotein (Aβ) sequence with familiar AD-associated mutations, and uricase knockout mouse (Uox-KO) which shows increased level of uric acid. To prevent renal failure caused by elevated uricnary excretion of uric acid, App-KI-Uox-KO mice were treated with allopurinol by dietary administration. We performed immunohistochemical staining for Aβwith anti-Aβ, astrocytes with anti-GFAP, and micloglia with anti-Iba1 using brain sections from 8 month-old mice. Aβ accumulation was increased in App-KI-UOX-KO mice in comparison with App-KI mouse. However, App-KI-Uox-KO mice displayed reduced astrocytosis and microgliosis in the cortex. Further studies are required to determine whether the glial changes are the cause or consequence of increased Aβ accumulation under higher uric acid level.